Construction of Stock Portfolios Based On K-means Clustering of Continuous Trend Features - Firmansyah, Hilmi; Rosadi, Dedi (Department of Matematics, Universitas Padjadjaran, 2024)
Optimal portfolio formation to reduce investment risk and increase returns is a concern for investors. There are various problems when investing with portfolio formation. First, it is difficult to select a pool of assets for portfolio formation. When the number of potential assets is relatively large, it will be difficult to select assets that fulfill portfolio formation and appropriate weights. Traditional portfolio theory such as